Beyond talent : creating a successful career in music - Beeching, Angela Myles (Oxford University Press, 2005)
Contrary to the standard joke about how to get to Carnegie Hall, "making it" in music is not simply about practice, practice, practice. Today, over 200,000 people in the United States work as musicians. With competition for traditional employment opportunities for musicians becoming ever more heated, today's musicians must know how the music industry works and how they can tailor their skills accordingly. How can musicians create their own professional paths?; In Beyond Talent, veteran music career counselor Angela Myles Beeching offers up a comprehensive guide for musicians in search of work, demystifying the steps to success. Drawing on a wealth of real-life examples, the book untangles artist management and the recording industry and explains how to find and create performance opportunities. Guidance is also provided on grant writing and fundraising, day jobs, freelancing, and how to manage money, time, and stress. Straightforward and reader-friendly, Beyond Talent is filled with practical tips, examples, checklists, sample budgets, goal-setting exercises, and extensive resource listings.; This essential handbook goes beyond the usual "how-to"; Beyond Talent helps musicians tackle the core questions about career goals, defining success, and imagining and then creating a meaningful life as a professional musician